Penerapan Metode Six Sigma dalam Menganalisa Pengendalian Kualitas Produk Beng-Beng pada Divisi Wafer PT Mayora Indah Tbk - Fahri Prastya (Pusat Riset dan Inovasi Nasional, 2024)
PT. Mayora Indah Tbk. (Company) was founded in 1977 with the first factory located in Tangerang with a target market in the Jakarta area and surrounding areas. PT Mayora Indah Tbk. has been able to prove itself to be one of the quality and high quality food producers and is called a market leader who has succeeded in creating a number of products that have pioneered each of these product categories. This company has several departments, one of which is the Production Department. Before conducting research, researchers first recorded all production defects for the period Mei 2023 – April 2024. Based on the results of research using the Six Sigma method, it was found that in the Production Department, the Wafer Division had the most defective products with a total of 63.460 pcs. Six Sigma implementation is an approach to improving product or service quality by reducing variability and process errors. This involves the steps Define, Measure, Analyze, Improve, and Control. Factors that cause production defects are caused by several things, including Man, Methods, Machine, Material and Environment